INSTRUCTIONAL STRATEGIES SELECTED BY TEACHER TO HELP MENTALLY RETARDED STUDENTS OF SPECIAL SCHOOL FOR THEIR ENGLISH VOCABULARY DEVELOPMENT (RETAIN, 2014)
Abstrak Penelitian ini ditujukan untuk mencari tahu apa sajakah strategi instruksional dari Marzano yang dipilih oleh guru untuk membantu perkembangan kosakata bahasa Inggris bagi siswa tuna grahita. Penelitian ini juga bertujuan untuk mencari tahu bagaimana guru menerapkan strategi instruksional yang telah dia pilih. Dasar dari penelitian ini menggunakan desain deskriptif kualitatif. Melalui beberapa observasi serta wawancara, peneliti menemukan bahwa dari delapan strategi instruksional dari Marzano, guru hanya memilih tujuh di dalam membantu perkembangan kosakata bahasa Inggris bagi murid tuna grahita di sekolah khusus. Strategi instruksionalyang dipilih tersebut adalah: identifying similarities, note taking, reinforcing effort and providing recognition, practice, nonlinguistic representation, setting objectives and providing feedback, and cues also questions. Di dalam satu pertemuan, guru mengkombinasikan lebih dari satu strategi instruksional. Semua strategi instruksional tersebut dipilih berdasarkan dari karakteristik para siswa tuna grahita yaitu; tidak mandiri, kurang mempunyai rasa percaya diri, lemah di dalam mengingat dan berpikir abstrak. Di dalam penerapan strategi instruksional yang dipilih, selama empat kali tatap muka, guru tidak melaksanakan satu teknik untuk satu kali pertemuan, namun guru menggunakan lebih dari satu strategi instruksional. Penerapan dari strategi instruksional yang dipilih oleh guru tersebut dibagi menjadi tiga tahapan kegiatan; pra, kegiatan inti dan pasca. Pada saat pra-kegiatan, guru lebih sering mengenalkan siswa kepada tujuan pembelajaran. Di dalam pasca-kegiatan, guru seringkali memotivasi siswa dengan memberikan beberapa nasihat. Sedangkan sisa dari strategi instruksional yang dipilih seperti; identifying similarities, note taking, providing recognition, practice, nonlinguistic representation, providing feedback, cues and questions, dilaksanakan pada kegiatan inti. Selebihnya, semua strategi instruksional yang terpilih beserta penerapannya adalah panduan bagi guru atau praktisi edukasi lainnya ketika berhadapan dengan murid tuna grahita, khususnya tentang perkembangan kosakata bahasa Inggris. Kata Kunci: Strategi Instruksional, murid tuna grahita, penerapan. Abstract This research is aimed to find out the teacher’s selection on Instructional strategies which are proposed by Marzano to help mentally retarded students of special education for their English vocabulary development. This research is also trying to find out how the teacher implemented his selections among Marzano’s instructional strategies. The base of this research is using descriptive qualitative as research design and through observations also interview, the researcher found out that among eight instructional strategies which are based on Marzano’s Instructional Strategies, the teacher choose only seven instructional strategies in helping mentally retarded students of special school for their English vocabulary development, they are: identifying similarities, note taking, reinforcing effort and providing recognition, practice, nonlinguistic representation, setting objectives and providing feedback, and cues also questions. In one meeting the teacher combines more than one instructional strategies. All of those instructional strategies were selected by the teacher based on students’ characteristics; dependent, less in confidence, weak in memorizing and thinking something abstractly. In implementing the selected instructional strategies, during four meetings the teacher did not use one technique for one meeting, but he used more than one instructional strategies in one meeting. The implementation of those selected instructional strategies was divided into three stages of activity, pre, whilst and post. The data from field notes show that in pre activity, the teacher mostly introduced the students to the lesson objective. In post activity, the teacher usually reinforced students’ effort by saying some advices to them. The rest of the selected instructional strategies; identifying similarities, note taking, providing recognition, practice, nonlinguistic representation, providing feedback, cues and questions, were conducted in whilst activity. Moreover, all of those selected instructional strategies and their implementation are the exemplary guides for the teachers or other educational practitioners when they are engaging with mentally retarded students at language competency, especially for English vocabulary development. Keywords: Instructional strategies, mentally retarded students, implementation